A caring and living environment that supports the spirituality of older people with dementia: A hermeneutic phenomenological study. (February 2023) - Toivonen, Kristiina; Charalambous, Andreas; Suhonen, Riitta
Abstract: Introduction: Meeting spiritual needs is an important part of the quality of nursing for older people living with dementia. The spirituality-supportive caring and living environment has rarely been studied, even though the environment plays an important role in supporting the well-being of older people with dementia. Aim: To further understanding about the spirituality-supportive elements of a caring and living environment from the perspective of older people with dementia and their family members. Design, setting and participants: We adapted hermeneutic phenomenology as a philosophical background and methodological approach in this study. After receiving the approval of the researcher's University Ethics Committee, a purposive sample of ten older people with dementia and their nine family members, in home care and long-term care settings in Southern Finland were recruited for interviews. Methods: An interview-based study was conducted using photography to collect the data. The in-depth interviews were conducted in dyads between September 2017 and March 2020 and transcribed verbatim. Thematic analysis was used to interpret the data. Results: Spirituality was seen as a continuum within human life, manifested through the environment even if older people with dementia were unable to express themselves. The spirituality experiences of the participants within the caring and living environment were summarized into three themes: "Where do I belong?", "What remains of me in the world?" and "Where am I going?" The older people, their family members and other people involved in their care provided a caring and living environment that supported spirituality with opportunities to seek answers to these questions through to the meaning of their life. Discussion and conclusions: This hermeneutic phenomenological study provides a new insight into the environment that supports the spirituality of older people with dementia. The elements of caring and living environment can remind older people with dementia of what supports their own way of thinking about spirituality and brings meaning to their life. Therefore, spirituality is worth of considering when planning a caring and living environment that supports what is important to the personhood of older people with dementia. Tweetable abstract : Spirituality is worth of considering when planning a caring and living environment that supports what is important to the personhood of older people with dementia.